Fuzzy Logic Control Strategy for Tracking the Maximum Power Point of a Horizontal Axis Wind Turbine. (2015) - Lakhal, Yassine; Baghli, Fatima Zahra; Bakkali, Larbi El
Abstract: Wind energy is affected by the stochastic nature of the wind speed, the purpose of this labor is to improve the machine's production efficacy. This control strategy estimates the restoring torque of generator adjusting the generator speed ratio, in this paper we will apply a fuzzy logic strategy to maximize the power by optimizing parameter adjusting on system, we consider in input of controller the wind speed and generator acceleration. Simulation results are given and discussed with MATLAB/SIMULINK to validate the proposed control strategy. This control strategy has a good performance in terms of dynamic response and steady property.